Inclusividade e efetividade no Conselho Estadual de Direitos Humanos do Espírito Santo (2009-2013) - Souza, Jaqueline Marcelino de (2014)
This dissertation analyzes the limits and possibilities of the Human Rights Council of Espírito Santo. By investigating the conditions of inclusiveness and effectiveness of local civil society demands, we verify how these conditions contribute to deepen democracy. The relevance of this work is justified by its ability to cooperate in the verification of the consequences of political participation of local civil society actors in participatory institution. In order to test the hypotheses raised, It was used a qualitative and quantitative methodology. Thus, the results obtained show that there is inside CEDH considerable amount of inclusiveness conditions in a variety of themes and people (civil society actors). However, as regards effectiveness, it refers more expressively to a participatory effectiveness in which the gains are scattered through the strengthening of civil society and attention to more specific issues than the implementing of public policies. Moreover, it was found that the judicialization of politics has been the most suitable strategy to overcome such obstacles in the participatory process concerning the implementation of human rights guarantee.